The environmental component of ESG factors from the standpoint of management in a closed-loop economy - E. V. Zhukova (Вестник университета)
Various approaches to the implementation of the concept of extended producer responsibility in the European Union are considered, and the features of the introduction and use of the closed-cycle economy in European countries are determined. Some examples of the impact of waste legislation on the production cycle of a product in the European Union are considered, as well as the main obstacles that manufacturers had to face when trying to introduce the extended producer responsibility concept in its current form into production. The key problems of using and implementing the concept under consideration in the economy are highlighted. The interrelation of ESG factors as guidelines for strategic development with the need for the development of mechanisms of extended producer responsibility is shown. The prospects for the development of extended producer responsibility in Russian production are also outlined.